2021
DOI: 10.1002/jcp.30568
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N‐oxide exacerbates acetaminophen‐induced liver injury by interfering with macrophage‐mediated liver regeneration

Abstract: Acetaminophen (APAP)-induced acute liver injury (AILI) is the most frequent cause of acute liver failure in developed countries. Trimethylamine N-oxide (TMAO) is a metabolite derived from the gut microbiota and is relatively high in the circulation of the elderly, individuals with diabetes, and heart disease. Herein, we showed that TMAO exacerbates APAP hepatotoxicity. It is possible that delayed liver repair and regeneration that resulted from reduced macrophage accumulation was responsible for this combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In RAW264.7 mouse macrophage cells, TMAO reduced MMP12 expression and suppressed cell migration across the transwell when stimulated by serum chemokines or lipopolysaccharide (LPS) (Yan et al, 2022). This finding contradicts the previous report where TMAO promoted RAW264.7 migration across the transwell upon stimulation by ox-LDL (Geng et al, 2018).…”
Section: Trimethylamine (Tma)contrasting
confidence: 65%
See 1 more Smart Citation
“…In RAW264.7 mouse macrophage cells, TMAO reduced MMP12 expression and suppressed cell migration across the transwell when stimulated by serum chemokines or lipopolysaccharide (LPS) (Yan et al, 2022). This finding contradicts the previous report where TMAO promoted RAW264.7 migration across the transwell upon stimulation by ox-LDL (Geng et al, 2018).…”
Section: Trimethylamine (Tma)contrasting
confidence: 65%
“…Yan et al investigated whether TMAO affects APAPinduced liver injuries. TMAO pretreatment (109 mg/kg intraperitoneal injection 2 h before 300 mg/kg of APAP intraperitoneal injection; attaining the maximum plasma concentration of ~200 M) exacerbated APAP-induced hepatotoxicity in mice (Yan et al, 2022). While the levels of CYP2E1 protein or oxidative stress markers were similar between control and TMAO-treated mice, more pronounced hepatic centrilobular sinusoidal hemorrhage and congestion at 12 h post-APAP were noted in TMAO-treated mice.…”
Section: Trimethylamine (Tma)mentioning
confidence: 94%
“…In this report, the oxidative stress response of liver tissue caused by APAP exposure was reflected in the depletion of GSH, the increase in MDA, 4-HNE, and CYP2E1 levels, which are in line with the previous studies. 19,20 The results showed that pretreatment with different doses of DHM reversed the exhaustion of liver GSH and the increase in MDA, 4-HNE, and CYP2E1 levels induced by APAP. Long-term or over-injection of APAP can cause hepatic sinusoidal macrophages to be activated and release a variety of pro-inflammatory cytokines, such as IL-1β and TNF-α.…”
Section: Discussionmentioning
confidence: 98%
“…45 Besides, MMPs participate in the synthesis of vitamin, trimethylamine, p-cresol, hydrogen sulfide and other metabolites, and in the transformation of exogenous active substances from drugs or plants, so as to promote host health or induce disease. [46][47][48][49][50] Therefore, to some extent, the health status of the gut can be predicted by assessing the abundance and distribution of the MMP family in the human gut microbiota. 51 How MMPs works in the gut?…”
Section: Discussionmentioning
confidence: 99%